The Role of Artificial Intelligence in Data-Driven Marketing: Enhancing Marketing Efficiency, Customer Engagement, and Business Performance in SMEs - Awad, Abdelrehim (Journal of Economics and Administrative Sciences, 2025)
Marketing applications of Artificial Intelligence (AI) have revolutionized business strategy providing Small and Medium-Sized Enterprises (SMEs) with superior customer engagement tools, strategic segmentation, and performance improvement. This study investigates the impact of marketing practices that are AI-based, like customer segmentation, predictive analytics, and marketing automation, on marketing efficacy, customer engagement, and on overall business performance in Egyptian small and SMEs. Utilizing a mixed-methods design, which means the integration of both quantitative (survey) and qualitative (interview) data analyzed with various methodological paradigms. The study consisted of structured surveys to 100 marketing professionals across several Egyptian SMEs and 30 executive interviews. Quantitative data were analyzed by regression analysis and ANOVA to verify associations, while thematic analysis was employed to analyze qualitative data. Regression analysis verified substantial positive impacts of AI adoption on company performance, customer engagement, and marketing effectiveness. ANOVA verified a significant difference in AI adoption among industries but not in company size. Thematic analysis verified significant findings about strategic adoption, technical and financial concerns, and opportunities for personalization.The results verify that AI integration is productive for SMEs in terms of marketing and operations, regardless of issues concerning resource limitation. This research adds to scholarly literature as well as practical models for adopting AI systems under resource-limited conditions.